Eksplorasi Tubuh Manusia Pada Eksperimental Fotografi - Ramadhan, Rizki (Institut Seni Indonesia Padangpanjang, 2022)
The human body is the entire human body that is visible from the tip of the toes to the tip of the head. The body is a perfect creation of God which is generally different. The creation of this work produces new forms of the human body which have a symbolic meaning. The body becomes a visual language or symbol that can represent various things about human life. Experimental photography is included in expression photography to discover something new, this experimental photography uses scanography technique as a medium for shooting without a camera with an emphasis on aesthetic expression. The creation of this work went through several stages, namely; preparation, design, embodiment, and presentation of works. The form referred to in this work is the external form of the human body, namely; shape, texture, and color. Scanography itself creates unique photo objects with special techniques in the process of creating photographic works without a camera. This creation uses digital imaging techniques that involve elements of digital photography with computer programs in the form of retouching, combining, and composing. The process is created from a series of cropping, resolution, dark and light processes, masking, contrast, and filters in the concept of digital imaging. The creation of the work on